COVID-19-associated encephalopathy: connection between neuroinflammation and microbiota-gut-brain axis - Duve, Khrystyna; Petakh, Pavlo; Kamyshnyi, Oleksandr (Frontiers in Microbiology, 2024)
While neurological complications of COVID-19, such as encephalopathy, are relatively rare, their potential significant impact on long-term morbidity is substantial, especially given the large number of infected patients. Two proposed hypotheses for the pathogenesis of this condition are hypoxia and the uncontrolled release of proinflammatory cytokines. The gut microbiota plays an important role in regulating immune homeostasis and overall gut health, including its effects on brain health through various pathways collectively termed the gut–brain axis. Recent studies have shown that COVID-19 patients exhibit gut dysbiosis, but how this dysbiosis can affect inflammation in the central nervous system (CNS) remains unclear. In this context, we discuss how dysbiosis could contribute to neuroinflammation and provide recent data on the features of neuroinflammation in COVID-19 patients.